Music in the castle of heaven a portrait of Johann Sebastian Bach - Gardiner, John Eliot 1943- (Lane, 2013)
Johann Sebastian Bach is one of the most famously unfathomable composers in the history of music. How can such sublime work have been produced by a man who (when we can discern his personality at all) seems so ordinary, so opaque - and occasionally so intemperate? John Eliot Gardiner grew up passing one of the only two authentic portraits of Bach every morning and evening on the stairs of his parents' house, where it hung for safety during the Second World War. He has been studying and performing Bach ever since, and is now regarded as one of the composer's greatest living interpreters. The fruits of this lifetime's immersion are now distilled in this remarkable book, which explains in wonderful detail how Bach worked, how his music is constructed, how it achieves its effects - and what it can tell us about Bach the man. It is grounded in all the most recent Bach scholarship but moves far beyond it, and takes us as deeply into Bach's works and mind as perhaps words can - a unique book about one of the greatest of all creative artists